Case report: ADHD and prognosis in tyrosinemia type 1 - Barone, Helene; Elgen, Irene Bircow; Bliksrud, Yngve Thomas; Vangsøy Hansen, Eirik; Skavhellen, Rita Rigmor; Furevik, Magne Ivar; Haavik, Jan (Frontiers in Psychiatry, 2023)
Neurometabolic disorders such as tyrosinemia type 1 (TYRSN1) may interfere with brain metabolism and give symptoms of attention deficit hyperactivity disorder (ADHD), also in patients treated with the enzyme inhibitor nitisinone (2-(2-nitro-4-trifluoromethylbenzoyl)-1,3-cyclohexanedione, NTBC). It has been reported that ADHD treatment improves treatment compliance, which is imperative for the long-term prognosis of patients with TYRSN1. Here, we report the case of a male patient who was diagnosed with TYRSN1 at three months of age and was subsequently treated with NTBC, restricted protein intake, and amino acids supplementation. At seven years of age, he was referred for neuropsychiatric assessment, diagnosed with ADHD, and treated with methylphenidate. The effects of the treatment were monitored via parental interviews, questionnaires covering ADHD symptoms, and a continuous performance test. A reduction in ADHD symptoms, particularly inattentiveness, was observed across all measures. The early identification of ADHD and the treatment of neurometabolic disorders, such as TYRSN1, may be important in a lifetime perspective as this may improve the prognosis of the medical condition as well.